Presentation, management, and clinical outcomes of acute type A dissection: Does sex matter?Central MessagePerspective - Frederike Meccanici, BSc; Carlijn G.E. Thijssen, MD, PhD; Arjen L. Gökalp, MD; Marie H.E.J. van Wijngaarden, MD; Mark F.A. Bierhuizen, MD; Guy F. Custers, MD; Jort Evers, BSc; Jolien A. de Veld, MD; Maximiliaan L. Notenboom, BSc; Guillaume S.C. Geuzebroek, MD, PhD; Joost F.J. ter Woorst, MD, PhD; Jelena Sjatskig, MD; et al. (JTCVS Open)
Background: Male–female differences in clinical presentation, management, and outcomes of acute type A aortic dissection (AD-A) have been reported; however, robust data are scarce. This study examined those differences. Methods: Consecutive adults diagnosed with AD-A between 2007 and 2017 in 4 referral centers were included retrospectively. Baseline data, operative characteristics, and mortality and morbidity during follow-up were collected using patient files, questionnaires, and referral information. Results: The study included 889 patients (37.5% female). Females were significantly older at presentation (median, 67.0 [interquartile range [IQR], 59.0-75.0] years vs 61.0 [IQR, 53.0-69.0] years; P < .001) and more often had cardiovascular comorbidities. Severe hypotension, tamponade, and nausea were more frequently observed in females. Short-term mortality was 18.5% in females and 21.2% in males (P = .362). No significant differences in treatment between males and females were observed. After surgery, the median follow-up was 6.2 years (IQR, 3.5-9.2 years). Overall 10-year survival was 50.1% (95% confidence interval [CI], 43.6%-57.6%) in females and 62.8% (95% CI, 58.1%-67.9%) in males (P = .009), although this difference was not significant after multivariable correction. Compared to the matched general population, survival was lower than expected in females and comparable to expected in males. The long-term reintervention rate in surgically treated survivors was comparable between males and females (2.1%/patient-year). Male- and female-specific risk factors for long term mortality were identified. Conclusions: These findings highlight a distinct clinical profile at presentation with AD-A between males and females, while treatment approach and short-term mortality were comparable. The relatively poor long-term survival in females and male-/female-specific risk stratification warrant further investigation.